ZAMANAGÓY BILIMLENDIRIW PROCESINDE KLASS BASShÍSÍNÍŃ ISKERLIGINE QOYÍLATUǴÍN TALAPLAR - Saytbekova, S. (SCIENCE and SOCIETY, 2025)
This article explores the role of the class teacher in the era of globalization and the modern requirements for their activities in the educational process. It emphasizes that the class teacher is not only responsible for monitoring students’ academic performance but also plays a crucial role in their upbringing, socio-psychological, and moral-spiritual development. The paper highlights the importance of innovative approaches such as the use of information technologies, project-based learning, learner-centered pedagogy, and the development of communicative competencies. The study concludes that improving the professional activities of class teachers is one of the urgent tasks of the modern education system.
Keywords: class teacher; modern education; innovative technologies; pedagogical approach; educational activity